INFLUENCE OF COMPETENCE AND APPLICATION LOCAL GOVERNMENT INFORMATION SYSTEM (SIPD) ENCOURAGING THE QUALITY OF FINANCIAL MANAGEMENT AT THE REGIONAL SECRETARIAT OF WEST JAVA PROVINCE - Susanti; Taufik Zulfikar; Zaenal Aripin (Journal of Jabar Economic Society Networking Forum, 2023)
The purpose of this study was to find out how competence affects the quality of financial management, to find out how the application of local government information systems affects the quality of financial management and to find out how competence and application of local government information systems affect the quality of financial management at the Regional Secretariat of West Java Province . The method used is descriptive research, namely research that is used to analyze a research result but is not used to make broader conclusions. So there are independent variables and dependent variables. The data collection technique used was field research using a questionnaire with 95 respondents and library research. Based on the results of research conducted by the author, it can be seen that there is a positive influence between competence and the application of local government information systems in encouraging the quality of financial management at the Regional Secretariat of West Java Province. Meanwhile, based on statistical calculations using SPSS, the correlation coefficient obtained was 0.683 and the Coefficient of Determination was 0.467 or 46.7% and had a significance level of less than 0.05 so it was proven that competence and SIPD implementation had an influence on the quality of financial management at the Regional Secretariat West Java province.